Correlation between body mass index and body circumference in children 4 to 10 year-old - Cossio-Bolaños, Marco Antonio (2010)
Objectives: To compare body mass index (BMI) with body circumferences in 4 to 10 year-old Brazilian children. Design: Descriptive correlational type study. Setting: Universidad Estatal de Campinas, Sao Paulo, Brazil. Participants: Children 4 to 10 year-old. Interventions: We selected in a probabilistic (stratified) manner a total of 517 children both sexes, 256 boys and 261 girls. We evaluated anthropometric measurements of body weight (kg), height (cm), BMI [BMI = weight (kg)/height (m)2] and relaxed mean arm girth, thigh and calf (cm). For data analysis descriptive statistics were used for arithmetic mean (X), standard deviation (SD) and Pearson’s coefficient correlation product moment (r) as well as to infer step by step the stepwise multiple regression analysis. Main outcome measures: Correlation of body mass index with body circumferences. Results: BMI had high correlation coefficients (r) with the three body circumferences. However, when simple statistical regression was applied, the best values were observed with the relaxed arm circumference (R2=0.74) for girls and children half calf (R2=0.70). In turn, when multiple regression was used (arm and calf) the level of explanation for girls increased to (R2=0.80) and children (R2=0.75), respectively. Conclusions: Arm circumferences and calf individually and together could be used as independent variables of BMI, since this index alone can not distinguish between overweight and excess fat in both gender children 4-10 year-old, especially when they are in the process of growth and somatic development.